PELATIHAN LITERASI KATA STAYCATION SEBAGAI IKLAN PROMOSI AKOMODASI PARIWISATA - Ni Made Rinayanthi (Sewagati, 2023)
This article analyzes the trend of using the word "staycation" through Bali hotel advertisements on Instagram. Staycation, which is a combination of the words "stay" and "vacation," refers to the concept of spending vacation time in the city or near where one lives. In this article, we use data from hotel advertisements in Bali posted on the Instagram platform to understand trends and patterns in the use of the word staycation. The research method used is descriptive qualitative by analyzing the content of hotel advertisements that use the word staycation in the text or ad description. The author collects and analyzes a number of Balinese hotel advertisements posted on their official Instagram accounts. The main focus of the analysis is to identify how often the word staycation is used, how the word is paired with the visual elements of the ad, and the context and marketing strategies associated with the use of the word. The results of the analysis show that the use of the word staycation in Bali hotel advertisements on Instagram has increased significantly in the last few years. This shows a growing trend among tourists who are looking for a relaxing and comfortable holiday experience without having to travel far from where they live. The use of the word staycation in these advertisements is usually reinforced by attractive visuals depicting pampering hotel facilities, beautiful swimming pools, and delicious food served on site.